Assessment of Introductory French Textbooks' Integration of Pronunciation - Fandre, Susan (My University, 2014)
The current research examines recurring issues related to the teaching and learning of French pronunciation, which is often overlooked in beginning courses. To evaluate the systematic integration of pronunciation material in such courses, the purpose of this study was to examine introductory French textbooks for references regarding French pronunciation.
Color poster with text, tables, and graphs.
Keywords: French pronunciation; Introductory French textbooks; Posters